DEVELOPMENT OF A SIMULATION PROJECT FOR AN INDUSTRIAL ENTERPRISE - Olga I. Babina (Статистика и экономика)
In the article, the questions of development of the simulation project for support of planning processes at the industrial enterprise are considered. The technique of application of simulation for support of planning processes at the industrial enterprise is offered. The comparative analysis of the most widespread approaches to the development of the simulation project for the industrial enterprise is carried out. The main roles in the simulation project, criterions of success, the cost and time of development of the project are defined.